GE_GERICHTE P/6153/2022 vom 13. Oktober 2022 - GE Cour de justice (2022)
EXPULSION(DROIT PÉNAL);RÉVOCATION DU SURSIS;SÉJOUR ILLÉGAL;STUPÉFIANT | LStup.19.al1.letc; LSTUP.19.al1.letd; LEI.115.al1.letb; CP.46; CP.66.alabis